Geographical and demographic clustering of gonorrhoea in London. Issue 6 (16th August 2007) - Risley, Claire L; Ward, Helen; Choudhury, Bhudipa; Bishop, Cynthia J; Fenton, Kevin A; Spratt, Brian G; Ison, Catherine A; Ghani, Azra C
Abstract : Background: Gonorrhoea is an important cause of sexual ill health and is concentrated in geographical areas and demographic groups. This study explores the distribution of gonorrhoea across London. Methods: Epidemiological data on all gonorrhoea cases were collected from 13 major genitourinary clinics in London between 1 June and 30 November 2004. Samples were stored centrally and typed using NG-MAST. The postcode of each case's main residence was used to calculate incidence of gonorrhoea by borough using data from the UK 2001 census and a population survey on residence of men who have sex with men (MSM). Results: 2891 cases were confirmed, 1822 of which had postcode data, resided in London, and had their strain successfully typed. There was a very high incidence of gonorrhoea in MSM (1834 per 100 000 population) and heterosexuals of black ethnicity (392 per 100 000). The incidence among heterosexuals was highest in City of London (390 per 100 000, 95% CI 213 to 566), Southwark (308 per 100 000, 95% CI 280 to 336), Hackney (284 per 100 000, 95% CI 254 to 313), and Lambeth (216 per 100 000, 95% CI 194 to 239) and was not associated with measures of social deprivation (correlation coefficient = 0.0008, p = 0.97) but was strongly associated with black ethnicity (correlation coefficient = 0.48, p = 0.01). 45% of cases had one of the 21 major strains; eight of these strains were significantly clustered geographically and persisted for a shorter duration than those that were not clustered. Patients travelled a mean of 7.7 km from their home to the clinic. Conclusions: High gonorrhoea incidence in London is observed in MSM and heterosexuals of black ethnicity. Endemic strains in both MSM and heterosexuals are diagnosed at multiple clinics. Interventions, including partner notification, must therefore operate between clinics.